Targeting abnormal ER stress responses in tumors: A new approach to cancer immunotherapy. (3rd March 2016) - Cubillos-Ruiz, Juan R.; Glimcher, Laurie H.
ABSTRACT: Cancers thrive under adverse conditions and simultaneously inhibit antitumor immunity. We recently found that endoplasmic reticulum (ER) stress responses driven by the IRE1α-XBP1 pathway not only promote cancer cell survival, but also provoke severe dendritic cell (DC) dysfunction in tumors. Targeting IRE1α-XBP1 represents a two-pronged approach to restrain malignant cells while eliciting concomitant antitumor immunity.